Climate Security Policy Coherence and Awareness Analysis Report: West Africa and Senegal - Pacillo, Grazia; Läderach, Peter R.D.; Schapendonk, Frans; Sarzana, Carolina; Scartozzi, Cesare M.; Savelli, Adam; Madurga Lopez, Ignacio M. (2022)
This report aims to contribute to this need by conducting a climate security policy coherence and awareness assessment of policy and strategy documents extracted from climate-and peace and security-related sectors produced at the national level in Senegal. It will do so by making use of a policy assessment framework developed specifically for the purpose of assessing coherence and climate security-sensitivity.